2021
DOI: 10.3390/v13122375
|View full text |Cite
|
Sign up to set email alerts
|

Possible Arbovirus Found in Virome of Melophagus ovinus

Abstract: Members of the Lipopteninae subfamily are blood-sucking ectoparasites of mammals. The sheep ked (Melophagus ovinus) is a widely distributed ectoparasite of sheep. It can be found in most sheep-rearing areas and can cause skin irritation, restlessness, anemia, weight loss and skin injuries. Various bacteria and some viruses have been detected in M. ovinus; however, the virome of this ked has never been studied using modern approaches. Here, we study the virome of M. ovinus collected in the Republic of Tuva, Rus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Earlier, it was suggested that Wifsystermes virus’ second ORF on the second segment requires the use of a variant genetic code, in which UGA is translated as tryptophan [ 7 ]. Here, and in our previous work [ 15 ], an alternative explanation was suggested for expression of the second ORF on the second segment in the novel solemo-like viruses. This ORF can be expressed via stop-codon codon read-through (a well-known mechanism of virus protein expression, typical for members of Polemovirus and Enamovirus (family Solemoviridae )) [ 21 ].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Earlier, it was suggested that Wifsystermes virus’ second ORF on the second segment requires the use of a variant genetic code, in which UGA is translated as tryptophan [ 7 ]. Here, and in our previous work [ 15 ], an alternative explanation was suggested for expression of the second ORF on the second segment in the novel solemo-like viruses. This ORF can be expressed via stop-codon codon read-through (a well-known mechanism of virus protein expression, typical for members of Polemovirus and Enamovirus (family Solemoviridae )) [ 21 ].…”
Section: Discussionsupporting
confidence: 64%
“…Two ORFs on the second segment are located in the same frame and are divided by a single stop codon (UGA). As a similar genome pattern is frequently found in other solemo-like viruses, it is likely that the second ORF on the second segment is expressed by stop codon read-through [ 1 , 2 , 15 ].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Sheep is the permanent host of M. ovinus ( Halos et al, 2004 ; Small, 2005 ; Kumsa et al, 2012 ; Liu et al, 2018 , 2019 ; Zhao et al, 2018 , 2020 ), but M. ovinus is also found in goats ( Bequaert, 1942 ; Seyoum et al, 2015 ), rabbits ( Small, 2005 ), dogs ( Tetley, 1958 ), donkeys ( Flores-Mendoza et al, 2021 ), European bison ( Izdebska, 2001 ), red foxes ( Lassnig et al, 1998 ), Tibetan sheep ( Hao et al, 2020 ), Tibetan antelope ( Liu et al, 2018 ; Zhao et al, 2018 , 2020 ) and humans ( Tetley, 1958 ). M. ovinus has a broad geographical distribution and is reported in Europe [e.g., Czechia ( Chrudimský et al, 2012 ; Nováková et al, 2015 ; Rudolf et al, 2016 ), Hungary ( Hornok et al, 2011 ), Slovakia ( Hubálek et al, 1986 ), Croatia ( Martinković et al, 2012 ), St Kilda ( Gibson et al, 2010 ), France ( Halos et al, 2004 ), Poland ( Werszko et al, 2021 ), Russia ( Litov et al, 2021 )], Africa [e.g., Ethiopia ( Kumsa et al, 2012 , 2014 ; Seyoum et al, 2015 ; Hadgu et al, 2021 ), Algeria ( Boucheikhchoukh et al, 2019 ), Kenya ( Liu et al, 2016 )], Oceania [e.g., Australia ( Liu et al, 2016 ; Litov et al, 2021 ), New Zealand ( Liu et al, 2016 )], North America [e.g., United States ( Halos et al, 2004 ; Kosoy et al, 2004 , 2016 )], South America [e.g., Peru ( Flores-Mendoza et al, 2021 )] and Asia [e.g., Turkey ( Payzin, 1953 ), Mongolia, India, Japan ( Liu et al, 2016 )]. In recent years, M. ovinus has frequently appeared in China, Asia in Tibet ( Chu et al, 2011 ), Gansu ( Duan et al, 2017 , 2020 ; Tang et al, 2018 ; Zhao et al, 2020 ), Xinjiang ( Liu et al, 2016 , 2017 , ...…”
Section: Introductionmentioning
confidence: 99%